Molecular Docking and Simulation Binding Analysis of Boeravinone B with Caspase-3 and EGFR of Hepatocellular Carcinoma - Krishnamoorthy, Praveen Kumar P.; Balaraman, Ashwini Devi; Priyadharshini, Annadurai; Shanmugam, Dharani A. S.; Muthukumaran, Sivanandham; Kesavamurthy, Amrutha; Revanasiddappa, Prasanna Diddige (Letters in Drug Design & Discovery, 2023)
Objective: Hepatocellular carcinoma (HCC) is a widely occurring cancer ranking second in humans, with an incidence rate of approximately 1.6% per year in India. Experimental analysis of the Boeravinones or the Rotenoids classification of compounds present in the roots of the Boerhaavia diffusa Linn plant has shown a wide range of anti-cancer activity against liver hepatoblastoma. Methods: Boeravinone B (BB) was screened from widely available Boeravinone A-E compounds based on a maximum drug-likeness score using Lipinski’s rule Five. BB was checked for anti-HCC activity by binding with the five receptors of VEGF, EGF, BCl2, Caspase-3 and Caspase-9 when compared with Sorafenib through molecular docking. GROMACS was used for simulating molecular dynamics. Results: BB has shown a negative maximum internal energy score of -8.04, -8.42, -6.66, -8.33 and -7.74 Kcal/mol when compared to Sorafenib’s internal energy score of -6.55, -7.12, -4.05, -5.48 and -6.12 Kcal/mol for VEGFR, EGFR, BCl2, Caspase-3 and Caspase-9 respectively. Simulation using GROMACS has revealed that RMSD results BB forms a more stable complex with the Caspase-3 and EGFR after 19s and 15s of simulation time. RMSF analysis has characterized local changes on 170-190 residues and 860- 900 residues in C-alpha atoms of BB-Caspase-3 and BB-EGFR complexes revealed protein flexibility. Conclusion: MMPBSA score of BB docked Caspase-3 and EGFR complexes were found to be -62.178 and -42.84 KJ/mol.
Keywords: hepatocellular carcinoma